La théorie générale des contrats. Pour sortir du dogmatisme - Belley, Jean-Guy (Les Cahiers de droit, 1985)
The general theory of contracts, as uniformly expressed by leading scholars in Quebec civil law, suffers from dogmatism. It rests on an individualistic and atomized notion of contract which is largely superceeded by the most significant forms of contemporary contractual practice. By focusing on the traditional rules of the Quebec Civil Code at the expense of more recent statutory law, the systematization it offers no longer corresponds to the state of the law of contracts. Refining the methods of the legal analysis, constructing typologies of contracts more sensitive to contractual practices, renewing dialogue with other disciplines such as history, economics and sociology would contribute, the author suggests, to stem the tide in authoritative writings away from its present dogmatism.